2018
DOI: 10.1016/j.enconman.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Loss development analysis of a micro-scale centrifugal compressor

Abstract: The ever-increasing demand for more efficient energy conversion has placed designers under increasing pressure to develop processing equipment that can meet contemporary needs. It has long been known that a decreasing Reynolds number has a negative effect on centrifugal compressor efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 40 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…This relation showed that at a low specific speed, efficiency drops due to an increase in the frictional losses in the vane passages and the disc friction. However, at a high specific speed, efficiency drops due to an increase in the aerodynamic losses resulted from the high relative velocity levels [15]. The specific speed expression is defined as follow Ns =…”
Section: Centrifugal Compressor Designmentioning
confidence: 99%
“…This relation showed that at a low specific speed, efficiency drops due to an increase in the frictional losses in the vane passages and the disc friction. However, at a high specific speed, efficiency drops due to an increase in the aerodynamic losses resulted from the high relative velocity levels [15]. The specific speed expression is defined as follow Ns =…”
Section: Centrifugal Compressor Designmentioning
confidence: 99%
“…Many models are modular, adding various losses introduced by various physical or endwall effects. One example is the tip clearance loss which was scrutinized both in experimental studies (Doustmohammadi et al , 2013; He and Zheng, 2018a, 2018b; Chaowei et al , 2019) as well as numerical ones (Tiainen et al , 2016, 2018; Chen and Gong, 2014; Yang et al , 2009). A theoretical framework is presented by Van den Braembussche (1984) showing the link between primary and secondary flows as well as blade count and endwall (hub and shroud) geometry shape.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the tip clearance on the turboexpander is also particularly significant, and the tip clearance loss is mainly concentrated on the suction surface of the induction wheel to the mid‐string section . Tiainen et al studied the development of Reynolds number loss in a centrifugal compressor without a vane diffuser and distinguished the losses caused by different causes. Soo‐Yong Cho et al experimentally studied the loss of incidence in different parts.…”
Section: Introductionmentioning
confidence: 99%